2014
DOI: 10.7860/jcdr/2014/6522.4129
|View full text |Cite
|
Sign up to set email alerts
|

Benign Hepatic Mesenchymal Hamartoma (HMH) – A Case Report

Abstract: A one-year-old male child presented with progressive enlargement of abdomen and loss of appetite which he had suffered from, since 4 months. Physical examination showed a palpable mass in right hypochondrium. Ultrasonography and MRI showed a solid mass arising from right lobe of liver. The resected mass was well encapsulated, yellowish white in colour and it measured 20 x 18 x 17cm. Cut surface showed a Nutmeg like appearance. Histology showed a well-defined, fibrous capsule with numerous ducts which were line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
4
0
5
Order By: Relevance
“…The mesenchymal components were composed mainly of architecturally abnormal biliary structures. [4][5][6][7] Therefore, both CK7 and CK19 were positive in most cases which indicates biliary epithelium in the cystic component. [8][9][10] Usually, there was limited immunoreactivity to CD34 and CD31 markers for hepatic mesenchymal hamartomas.…”
Section: Discussionmentioning
confidence: 97%
“…The mesenchymal components were composed mainly of architecturally abnormal biliary structures. [4][5][6][7] Therefore, both CK7 and CK19 were positive in most cases which indicates biliary epithelium in the cystic component. [8][9][10] Usually, there was limited immunoreactivity to CD34 and CD31 markers for hepatic mesenchymal hamartomas.…”
Section: Discussionmentioning
confidence: 97%
“…Karaciğerin mezenkimal hamartomu, malforme safra kanalları ve miksomatöz mezenkimin proliferasyonu ile karakterize benign bir karaciğer tümörüdür (7) . Kitlede kistik yapılar baskındır, arada solid yapılar da içerir ve gerçek bir kapsülü yoktur.…”
Section: Discussionunclassified
“…Mezenkimal hamartoma özgü bir laboratuvar bulgusu yoktur. Karaciğer fonksiyon testleri, AFP ve βhCG yüksek bulunabilir (6,7) . AFP tümör belirteci olarak kullanılabilir, tümör içerisindeki prolifere hepatositlerden salındığı düşünülmektedir (7) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Whether BDH has malignant potential remains controversial. BDH was previously considered as a benign liver tumor that should be followed regularly (11,(24)(25)(26). However, an increasing number of cases indicated that BDH may transform to cholangiocarcinoma and hepatocellular carcinoma (3,4,10,27-29).…”
Section: Discussionmentioning
confidence: 99%